(untitled) (Publicaciones en Ciencias y Tecnología, 2019)
The ingots of CuTaAlSe3 and CuTaGaSe3 were synthesized using the melt and annealing technique. X-Ray Diffraction (XRD) and Differential Thermal Analysis (DTA) techniques were used for characterization of the alloy. The analysis of the diffraction pattern indicates that both samples are composed by two phases; the mean phase indexes as a hexagonal structure, whereas the secondary phase indexes as a tetragonal chalcopyrite-like structure. From the shape of the DTA peaks for the CuTaAlSe3 and CuTaGaSe3 alloys, was deduced that the melting is incongruent for both materials, value of 1348K and 1235K, respectively.